LncRNA HULC mediates radioresistance via autophagy in prostate cancer cells - Chen,Changxuan (2018)
Prostate cancer (PCa) is the second leading cause of cancer death in men. Irradiation is one of the available options for treatment of PCa, however, approximately 10–45% of PCa are resistant to irradiation. We aimed to explore the role of long non-coding RNA highly upregulated in liver cancer (HULC) in the sensitivity of PCa cells to irradiation. Survival rate, cell apoptosis, cycle, expressions of related proteins, and caspase-3 activity were assessed to explore the effects of HULC on sensitivity of PCa cells to irradiation. Expression of HULC in DU-145, PC3, LNCaP, and RWPE-1 cells was determined and the influence of HULC on DU-145 cells was explored. Then, PC3 cells aberrantly expressing HULC were implanted into NOD-SCID mice for tumor xenograft study. Changes of autophagy after aberrant expression of HULC in vivo and in vitro were tested. Furthermore, the interacted protein of HULC and involved signaling pathway were investigated. In PC3 and LNCaP cells under irradiation, survival rate and cell cycle were decreased and apoptosis was increased by HULC knockdown. HULC knockdown arrested PC3 cells at G0/G1 phase. DU-145 was sensitive to irradiation, and resistance to irradiation of DU-145 cells was enhanced by HULC overexpression. Moreover, HULC knockdown enhanced the sensitivity of PC3 xenografts to irradiation. HULC knockdown promoted autophagy through interaction with Beclin-1 and inhibition of mTOR, resulting in increased apoptosis. HULC knockdown improved sensitivity of PCa cells to irradiation both in vivo and in vitro. HULC suppressed Beclin-1 phosphorylation, thereby reduced autophagy, involving the mTOR pathway.